Re-imagining the church implications of being a people in the world - Suderman, Robert J.; Suderman, Andrew Gregory (Eugene, Oregon : Wipf & Stock Publishers, 2016)
The church. What has it become? What was it meant to be? Does it pave the way or get in the way? Are we suspicious of the institutionalization of church bureaucracy? Or thrilled with the relevant impact of its presence?Robert J. Suderman writes about the church as a practitioner. His inspiration emerges out of the crossroads of biblical vision and human sincerity always tempered with frailty. Years of ministry, never a stranger to complexity, only serve to sharpen the vision of possibility. His imagination of what can be is never divorced from the realities of what is. He does not bow to the c.
Keywords: Church; Church work; Mennonites -- Doctrines; RELIGION / Christian Theology / Ecclesiology; Electronic books